The Impact of Structural Gender Differences and its Consequences on Access to Energy in Rural Bangladesh - Fatema, Naureen (World Bank, Washington, DC, 2012)
This report studies the impact that gender differences in Bangladesh have on access to energy and energy services and the consequences of these impacts based on review of recent literature on the matter. The report concludes that the structural gender differences that arise from cultural and religious norms can lead to various impacts in access to energy services which in turn can have long term consequences on women and all these factors must be considered while designing rural energy- gender projects.